Development of small agrobusiness subjects and governmental support - Antonina Aleksandrovna Pakhomova (Экономика региона, 2011)
This paper reveals the importance and role of state support for the development of agrobusiness in Russia. Public support in different countries was monitored and major vulnerabilities of small agrobusinesses were revealed. The study aims to review and develop conceptual positions and scientific and practical recommendations aimed at improving the efficiency of state support of small agrobusinesses. The scientific novelty of this research is to develop theoretical and practical recommendations on the formation of areas of state supported agrobusiness plus infrastructure development of small agrobusiness. Small agrobusiness can effectively solve many problems in the industrial, social, scientific and economic nature of the agricultural sector and rural areas. It creates the necessary atmosphere of competition and rapidly responds to changes in market conditions, provides the necessary market conditions in the mobility actions and also promotes cooperative production development.